Relationship Between Belowground Carbon Allocation and Nitrogen Uptake in Saplings Varies by Plant Mycorrhizal Type - Keller, Adrienne B.; Phillips, Richard P. (Frontiers in Forests and Global Change, 2019)
While it has long been hypothesized that belowground carbon (C) allocation in plants is tightly coupled to nutrient uptake, empirical tests of this are rare, especially for woody plants. We grew tree saplings of nine species in soils enriched in isotopically-labeled nitrogen (N) and after several months, pulse-labeled trees with 13CO2. This approach allowed us to track how 13C allocation from foliage to absorptive root tissue related to 15N movement from soil to plant tissues as a measure of each species’ N return on C investment. We hypothesized that tree species known to associate with ectomycorrhizal (ECM) fungi would have greater belowground C fluxes than those that associate with arbuscular mycorrhizal (AM) fungi, and that species with greater belowground C allocation would acquire the most soil N. Overall, we found large interspecific differences in both the amount of recently-fixed C allocated belowground and plant N uptake, yet no differences in either flux between AM and ECM trees (P > 0.05). Moreover, we found no differences between mycorrhizal groups in terms of their N return on C investment. However, mycorrhizal type influenced the relationship between belowground C allocation and N uptake, which was positive in AM species (r = 0.42; P =0.001) and negative in ECM species (r = -0.44; P =0.003), suggesting that the relationship between C allocation and plant nutrition is more complex than theory predicts. Collectively, our results suggest that tree species’ nutrient return on C investment can differ greatly among species, and that efforts to model these dynamics should consider the traits and tradeoffs that underlie these dynamics.